Analysis of patients (pts) with unresectable hepatocellular carcinoma (uHCC) and Child-Pugh (CP)-B liver function treated with regorafenib in routine clinical practice in the observational REFINE study - Merle, Philippe; Finn, Richard S.; Kudo, Masatoshi; Klümpen, Heinz-Josef; Lim, Ho Yeong; Pinter, Matthias; Babajanyan, Svetlana; Khan, Javeed; Awan, Maria; Özgürdal, Kirhan; Qin, Shukui (Journal of clinical oncology, 2024)
452Background: Pts with HCC and compromised liver function are typically excluded from clinical trials. The REFINE real-world study (NCT03289273) assessed a more varied pt population treated with regorafenib than the phase 3 RESORCE trial.1 Median overall survival (OS) in REFINE was 13.2 months and treatment-emergent adverse events (TEAEs) were consistent with RESORCE. We present a subgroup analysis of outcomes in pts from REFINE with CP-B liver function. Methods: REFINE is an international, prospective observational study of pts with uHCC for whom the decision to treat with regorafenib according to the local health authority approved label was made by their physician before enrollment. The primary endpoints were safety (Medical Dictionary for Regulatory Activities v25) and dose modifications due to drug-related TEAEs. Secondary endpoints included OS and duration of treatment (DoT). Results: Of 1005 evaluable pts, 123 (12%) were classified as CP-B at study entry, with most being CP-B7 (Table). Of the CP-B pts, 40/123 (9%), 9/123 (18%), and 58/123 (15%) initiated regorafenib at 160 mg, 120 mg, and 80 mg, per day, respectively. Median DoT with regorafenib was 2.3 months in CP-B pts and 3.7 months in the overall cohort. Incidence rates of TEAEs in CP-B pts and the overall cohort were similar (93% and 92%) and TEAEs were drug-related in 70% and 74% of pts, respectively. Grade 3-4 TEAEs occurred in 41% of CP-B pts and 39% of the overall cohort and were drug-related in 27% and 26% of pts, respectively. Serious TEAEs were observed in 48% of CP-B pts and 37% of the overall cohort, and were drug-related in 11% and 9% of pts, respectively. Drug-related TEAEs led to less frequent dose modifications in CP-B pts than in the overall cohort (28% vs 37%), but more frequent permanent discontinuations (28% vs 16%). Median OS in CP-B pts was 6.3 (95% confidence interval [CI] 4.9, 7.8) months and in CP-B7 pts was 6.7 (95% CI 5.1, 8.7) months. Conclusions: In REFINE, pts with uHCC and CP-B liver function had similar rates of grade 3-4 TEAEs, but a higher occurrence of serious TEAEs due to underlying cirrhosis led to more frequent permanent discontinuations in CP-B pts. Median OS in CP-B7 pts was comparable with OS in CP-B pts overall. The evaluation of prognostic models to identify CP-B pt subgroups who may benefit from regorafenib treatment is a subject for further research. 1. Kim YJ, ILCA 2022. Characteristics at Study EntryCP-B(n=123)CP-B7(n=84)All pts(N=1005)Asian/non-Asian, %46/5455/4555/45ECOG performance status ≥2, %13126BCLC stage B/C, %11/7312/7513/62Alcohol use, %424025Hepatitis B, %273038Hepatitis C, %232324Vascular invasion, %435734Metastases, %504559Initial regorafenib dose as 160/120/80 mg per day, %9/18/156/13/1047/11/40Median time from initial uHCC diagnosis to regorafenib start, months17.417.124.7